2019
DOI: 10.1111/jcpt.13072
|View full text |Cite
|
Sign up to set email alerts
|

Initial dose optimization of tacrolimus for children with systemic lupus erythematosus based on theCYP3A5polymorphism and coadministration with Wuzhi capsule

Abstract: What is known and objectives Tacrolimus, an immunosuppressant, has been used to treat paediatric systemic lupus erythematosus, but the optimal initial regimen is not clear. The purpose of this study was to explore the optimal initial dose of tacrolimus for children with systemic lupus erythematosus using population pharmacokinetics and pharmacogenomics. Methods Clinical information, tacrolimus concentrations and related genetic polymorphisms were incorporated into a model using non‐linear mixed‐effects modelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 72 publications
(123 reference statements)
0
15
0
Order By: Relevance
“…The clinical information of 32 pediatric and adolescent patients with LN (5 males and 27 females) was collected for the present study and was used for population modelling. The clinical information of certain patients was collected in previous studies (13,14). Table I presents patient characteristics and drug combinations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical information of 32 pediatric and adolescent patients with LN (5 males and 27 females) was collected for the present study and was used for population modelling. The clinical information of certain patients was collected in previous studies (13,14). Table I presents patient characteristics and drug combinations.…”
Section: Resultsmentioning
confidence: 99%
“…The clinical information was collected from the hospital's information system and tacrolimus whole-blood levels were acquired from a therapeutic drug detection system. Partial basic clinical information data with partial overlap were collected from certain patients in previous studies (13,14). The present study was approved by the Research Ethics Committee of the Children's Hospital of Fudan University [ethical approval code: (2019)020].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tacrolimus is a first‐line immunosuppressant that has been widely used for liver, 18 kidney, 19 haematopoietic stem cell transplantations, 20 systemic lupus erythematosus, 21 lupus nephritis 22 and other diseases. The use of tacrolimus for the treatment of lupus nephritis, especially proteinuria, can be significantly reduced 23‐32 .…”
Section: Discussionmentioning
confidence: 99%
“…Since there is no significant dose‐response relationship, clinical efficacy is rarely measured by tacrolimus dose; instead, the drug concentration is controlled within a certain range. Many studies have reported that the clinical use of tacrolimus in transplantation, 51 nephrotic syndrome 52 and SLE 21 was also based on maintaining the concentration within a certain range using therapeutic drug monitoring. In fact, many drugs in combination can affect the metabolism of tacrolimus, and the advantage of using the tacrolimus window in this study is that we can adjust its flexible dose to keep the concentration within the window through routine therapeutic drug monitoring, simplifying the complex clinical problems.…”
Section: Discussionmentioning
confidence: 99%